Qualitative and Computational Analysis of a Mathematical Model for Tumor-Immune Interactions - F. A. Rihan; M. Safan; M. A. Abdeen; D. Abdel Rahman (Journal of Applied Mathematics)
We provide a family of ordinary and delay differential equations to model the dynamics of tumor-growth and immunotherapy interactions. We explore the effects of adoptive cellular immunotherapy on the model and describe under what circumstances the tumor can be eliminated. The possibility of clearing the tumor, with a strategy, is based on two parameters in the model: the rate of influx of the effector cells and the rate of influx of IL-2. The critical tumor-growth rate, below which endemic tumor does not exist, has been found. One can use the model to make predictions about tumor dormancy.